Regional variations in the prevalence and misdiagnosis of air flow obstruction in China: baseline results from a prospective cohort of the China Kadoorie Biobank (CKB). Issue 1 (9th May 2014) - Kurmi, Om P; Li, Liming; Smith, Margaret; Augustyn, Mareli; Chen, Junshi; Collins, Rory; Guo, Yu; Han, Yabin; Qin, Jingxin; Xu, Guanqun; Wang, Jian; Bian, Zheng; et al.
Abstract : Background: Despite the great burden of chronic respiratory diseases in China, few large multicentre, spirometry-based studies have examined its prevalence, rate of underdiagnosis regionally or the relevance of socioeconomic and lifestyle factors. Methods: We analysed data from 512 891 adults in the China Kadoorie Biobank, recruited from 10 diverse regions of China during 2004–2008. Air flow obstruction (AFO) was defined by the lower limit of normal criteria based on spirometry-measured lung function. The prevalence of AFO was analysed by region, age, socioeconomic status, body mass index (BMI) and smoking history and compared with the prevalence of self-reported physician-diagnosed chronic bronchitis or emphysema (CB/E) and its symptoms. Findings: The prevalence of AFO was 7.3% in men (range 2.5–18.2%) and 6.4% in women (1.5–18.5%). Higher prevalence of AFO was associated with older age (p<0.0001), lower income (p<0.0001), poor education (p<0.001), living in rural regions (p<0.001), those who started smoking before the age of 20 years (p<0.001) and low BMI (p<0.001). Compared with self-reported diagnosis of CB/E, 88.8% of AFO was underdiagnosed; underdiagnosis proportion was highest in 30–39-year olds (96.7%) compared with the 70+ age group (81.1%), in women (90.7%), in urban areas (89.4%), in people earning 5K–10 K ¥ monthly (90.3%) and in those with middle or high school education (92.6%). Interpretation: In China, the burden of AFO based on spirometry was high and significantly greater than that estimated based on self-reported physician-diagnosed CB/E, especially in rural areas, reflecting major issues with diagnosis of AFO that will impact disease treatment and management.